Alterations in the Gut Microbiome and Cecal Metabolome During Klebsiella pneumoniae-Induced Pneumosepsis - Wu, Ting; Xu, Fangming; Su, Cong; Li, Hongru; Lv, Na; Liu, Yanyan; Gao, Yufeng; Lan, Yanhu; Li, Jiabin (Frontiers in Immunology, 2020)
Klebsiella (K.) pneumoniae is a common cause of pneumonia-derived sepsis in human and is associated with high morbidity and mortality. The microbiota promotes and maintains host immune homeostasis during bacterial infections. However, mechanisms by which the gut microbiota affects immune responses in the lung still remain poorly understood. Here, we performed cecal metabolomics sequencing and fecal 16s rRNA sequencing in K. pneumoniae-infected mice and uninfected controls, and showed that K. pneumoniae infection led to profound alterations in the gut microbiome and thus cecal metabolome. We further demonstrated that Lactobacillus reuteri and Bifidobacterium pseudolongum, which promote butyric acid production, could be used as biomarkers for K. pneumoniae-induced pneumonia. Spearman correlation analysis showed that alterations in the richness and composition of gut microbiota were associated with profound changes in host metabolite concentrations. Then, short chain fatty acids (SCFAs), including acetate, propionate and butyrate, were detected in feces and blood samples by gas chromatography-mass spectrometry (GC-MS). Consistent with the metabolomics data, we observed that concentrations of these three SCFAs were all lower in the infected groups than in the untreated controls. Lastly, oral supplementation with these three SCFAs reduced susceptibility to K. pneumoniae infections, as indicated by lower bacterial burdens in the lung and higher survival rates. Our data highlights the protective roles of gut microbiota and certain metabolites in K. pneumoniae-pneumonia, and suggests that it is possible to intervene in this bacterial pneumonia by targeting the gut microbiota.